How did the US economy react to shale gas production revolution? An advanced time series approach - SÜALP, MUSTAFA NEDİM (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This paper aims at examining the impacts of shale gas revolution on industrial production in the US. To this end, this paper, first, throughout literature review, exposes the features of shale gas revolution in the US in terms of energy technology and energy markets. However, the potential influences of shale gas extraction on the US economy are not explicit in the existing literature. Thus, considering mainly the output of shale gas revolution on the US economy in this research, later, the paper conducts econometric models to reveal if there exists significant effect(s) of shale gas revolution on the US economy. Therefore, the paper employs unit root tests and cointegration tests by following relevant US monthly data from January 2008 to December 2013. Then, this paper observes long run impact of shale gas production on industrial production in the US through dynamic ordinary least squares estimation with dummy structural breaks and conducts Granger causality test based on vector error correction model. The dynamic ordinary least squares estimator explores that shale gas production has a positive effect on industrial production. Besides, the Granger causality test presents that shale gas production Granger causes industrial production in the long run. Based on the findings of the long run estimations, the paper yields that industrial production is positively related to shale gas production. Eventually, upon its findings, this paper asserts that (i) the shale gas revolution in the US has considerable positive effects on the US economy within the scope of the validity of the growth hypothesis, (ii) new technologies might be developed to mitigate the possible negative environmental effects of shale gas production, (iii) the countries having shale gas reserves, as in US, may follow energy policies to utilize their shale reserves more in the future to meet their energy demand and to increase their economic welfare. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Shale gas revolution; The US economy; Impact of shale gas; Cointegration; Causality; Structural breaks; RENEWABLE ENERGY-CONSUMPTION; UNIT-ROOT TESTS; CO2 EMISSIONS; ELECTRICITY CONSUMPTION; CAUSAL RELATIONSHIP; GRANGER CAUSALITY; GROWTH NEXUS; COINTEGRATION; IMPACT; PANEL